Trends of maternal health service coverage in the Democratic Republic of the Congo: a pooled cross-sectional study of MICS 2010 to 2018 - Fuyu Guo; Xinran Qi; Huayi Xiong; Qiwei He; Tingkai Zhang; Siyu Zou; Hanyu Wang; Rie Takesue; Kun Tang (BMC, 2021)
Abstract Background Maternal health services are essential for reducing maternal and newborn mortality. However, maternal health service status in the Democratic Republic of the Congo (DRC) remains poorly understood. This study aims to explore the trends of antenatal care (ANC) and skilled birth attendance coverage in the past decade in the DRC. Methods The 13,361 participants were from two rounds of Multiple Indicators Cluster Survey (MICS) conducted by the National Institute of Statistics of the Ministry of Planning of the DRC, in collaboration with the United Nations Children's Fund (UNICEF), in 2010 and 2017-2018. A regression-based method was adopted to calculate adjusted coverage of ANC and skilled birth attendance. Subgroup analysis based on different socioeconomic status (SES) was conducted to explore the impact of domestic conflicts. Results From 2010 to 2018, the overall weighted ANC coverage in the DRC declined from 87.3 % (95 % CI 86.1-88.0 %) to 82.4 % (95 % CI 81.1-84.0 %), while the overall weighted skilled birth attendance coverage increased from 74.2 % (95 % CI 72.5-76.0 %) to 85.2 % (95 % CI 84.1-86.0 %). Adjusted ANC coverage and adjusted skilled birth attendant coverage both declined in Kasai Oriental, but increased in Nord Kivu and Sud Kivu. In Kasai Occidental, ANC coverage declined, but skilled birth coverage increased. In the Kasai region, the largest decline in adjusted coverage of ANC was found among the poorest women. However, in the Kivu region, both the adjusted coverage of ANC and skilled birth attendance increased among the poorest women. Conclusions Due to ongoing conflicts, there has been a systemic deterioration of maternal healthcare coverage in some regions of the DRC, particularly among people with low SES. However, in other regions, maternal healthcare services were not severely disrupted possibly due to substantial international health assistance.